Empowering EFL Learners’ Writing Skills through the Employment of Automated Peer Feedback - Wijaya, Kristian; Iliasu, Samuel Femi; Obi, Sabina Nwakaego (Universitas PGRI Semarang, 2025)
Effective feedback provision is essential for enhancing EFL learners’ writing proficiency. Therefore, second language educators need to explore more varied and productive approaches to delivering writing feedback that supports learners’ continuous development. In this regard, the integration of automated peer feedback has emerged as a significant innovation in modern second language writing instruction. It enables learners to acquire richer insights, linguistic knowledge, and writing competencies through digitally mediated peer commentaries. This library-based study employed thematic analysis to examine 30 previously published studies on automated peer feedback. The analysis allowed the researcher to identify recurring themes and interpret relevant findings systematically. The main objective of this investigation was to explore how automated peer feedback empowers EFL learners’ writing skills. The findings revealed that automated peer feedback enhances learners’ writing development by fostering student-centered engagement and collaborative learning environments.